IMPLEMENTASI DESIGN THINKING PADA STRATEGI PENGEMBANGAN PRODUK KRIYA - Yahya, Disha Dwi; Yuana, Pusvita (Jurnal Kewirausahaan dan Inovasi, 2023)
Appropriate product development strategy will place a craft industry player into a more superior position in the competition. Sae Japara is a craft business that produces furniture made from wood, glass, and rattan. This company is required to make product developments in order to survive in the craft business competition. This research aims to generate options for the company to help it develop craft products by implementing design thinking. This descriptive qualitative study was conducted through phases of definition, research, interpretation, ideation, prototyping, and evaluation. The data was harvested from interviews, observations, and documentation. The results of the analyses produced three craft product development ideas suitable for the need and the preference of Sae Japara’s target customers. They are rattan make-up container, wood-framed mirror with board addition, and rattan-framed mirror. Those products are customizable in size and color. Further, this research proves that design thinking can help the development of craft products that are high in quality and relevant with customer’s need and preference.